The longitudinal effects of maternal parenting practices on children's body mass index z-scores are lagged and differential - Lisa Kakinami; Prince Kevin Danieles; Fatemeh Hosseininasabnajar; Tracie A. Barnett; Mélanie Henderson; Andraea Van Hulst; Lisa A. Serbin; Dale M. Stack; Gilles Paradis (BMC, 2023)
Abstract Background The longitudinal relation between parenting practices and styles with children's body mass index z-scores (zBMI) is poorly understood. Previous studies suggest the relationship may be complex, but small samples and short follow-ups diminish the strength of the evidence. The objectives of this study were to investigate whether the relationship is bidirectional, time-varying, and lagged using data from a large, representative birth cohort of Quebec children. Methods Data were from the Québec Longitudinal Study of Child Development (QLSCD), a prospective birth cohort (n = 1,602). The mothers' interactions with their children (at ages 6, 8, 10, and 12 years) were utilized in factor analysis to identify three latent parenting practices (disciplinarian, lenient, and responsive). The parenting practices were analyzed with K-means clustering to identify the parenting styles. The temporal and bidirectional relationships were assessed in a cross-lagged path analysis using a structural equation modelling framework. Mixed models controlling for age, sex, income, mother's education, and whether the participant was first-born were estimated. Missing data were handled with full information maximum likelihood. Results From the linear mixed models, greater lenient and responsive parenting practices were associated with higher zBMI (B = 0.03, p < 0.05) two years later. However, there was no evidence that the relationship was bidirectional nor that parenting style was predictive of children's zBMI. Conclusion While mothers' parenting practices were unaffected by their children's zBMI, parental practices were predictive of future zBMI among their prepubertal children. More in-depth exploration of parenting practices and their potential impact on pediatric weight is needed.